1986
DOI: 10.1055/s-2007-969164
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Shashen (Adenophora axilliflora)

Abstract: From the ethyl acetate extract of the Chinese drug "Shashen", the root of Adenophora axilliflora Borb., three triterpenoids, cycloartenol acetate ( 1), lupenone ( 2) and beta-sitosterol ( 3), two triterpenoid derivatives, beta- D-glucopyranosyl-(1-->3)-beta-sitosterol ( 7) and its 6- O-palmitoyl ester ( 6), along with two coumarins, (+)-praeruptorin A ( 4) and 3'-angeloyl-4'-isovaleryl-(3' S, 4' S) CIS-khellactone ( 5) have been isolated. A detailed (1)H-NMR analysis of compounds 6, 7 and their acetates is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The molecular formula depicts the presence of six degrees of unsaturation, out of them one can be satisfied by an olefinic function. The presence of seven methyl singlets and an olefinic function in the 1H-NMR spectrum revealed that Lupeol is pentacylic triterpenoidal type in nature [6, 15]. Study conducted by Martelanc et al, using high-performance liquid chromatographic (HPLC) method with UV and mass spectrometric [MS] showed that Lupeol exhibits a parent ion peak at m/z 409 [M+H-18][+]] [16].…”
Section: Chemical Structure and Analysismentioning
confidence: 99%
“…The molecular formula depicts the presence of six degrees of unsaturation, out of them one can be satisfied by an olefinic function. The presence of seven methyl singlets and an olefinic function in the 1H-NMR spectrum revealed that Lupeol is pentacylic triterpenoidal type in nature [6, 15]. Study conducted by Martelanc et al, using high-performance liquid chromatographic (HPLC) method with UV and mass spectrometric [MS] showed that Lupeol exhibits a parent ion peak at m/z 409 [M+H-18][+]] [16].…”
Section: Chemical Structure and Analysismentioning
confidence: 99%
“…The presence of seven methyl singlets and an olefinic function in the 1 HNMR spectrum reveals that lupeol is of pentacylic triterpenoidal type in nature. [18] Study conducted by Martelanc et al, using high-performance liquid chromatographic (HPLC) method with UV and mass spectrometry (MS), showed that lupeol exhibits a parent ion peak at m/z 409 [M + H+-18. [18] An overview of lupeol and its beneficial effects…”
Section: Chemical Structure and Analysismentioning
confidence: 99%
“…They have a wide geographical distribution range including Japan, China, Korea, Taiwan and Russia. Previously, it was reported that Adenophorae Radix contains triterpenoids (Du et al ., ; Yao et al ., ), phenolic glycosides (Kuang et al ., ; Koike et al ., ), sterols, alkaloids (Asano et al ., ) and essential oils (Miyazawa et al ., ). Anti‐obesity (Choi et al ., ), anti‐oxidant (Kim et al ., ; Kim et al ., ), anti‐cancer (Lee et al ., ) and anti‐bacterial (Huang, ) activities have been reported for the extract of Adenophorae Radix.…”
Section: Introductionmentioning
confidence: 99%